Analytical and Clinical Performance of Amyloid-Beta Peptides Measurements in CSF of ADNIGO/2 Participants by an LC–MS/MS Reference Method. (31st January 2020) - Korecka, Magdalena; Figurski, Michal J; Landau, Susan M; Brylska, Magdalena; Alexander, Jacob; Blennow, Kaj; Zetterberg, Henrik; Jagust, William J; Trojanowski, John Q; Shaw, Leslie M; ,
Abstract: Background: Cerebrospinal fluid (CSF) amyloid-β1-42 (Aβ42) reliably detects brain amyloidosis based on its high concordance with plaque burden at autopsy and with amyloid positron emission tomography (PET) ligand retention observed in several studies. Low CSF Aβ42 concentrations in normal aging and dementia are associated with the presence of fibrillary Aβ across brain regions detected by amyloid PET imaging. Methods: An LC–MS/MS reference method for Aβ42, modified by adding Aβ40 and Aβ38 peptides to calibrators, was used to analyze 1445 CSF samples from ADNIGO/2 participants. Seventy runs were completed using 2 different lots of calibrators. For preparation of Aβ42 calibrators and controls spiking solution, reference Aβ42 standard with certified concentration was obtained from EC-JRC-IRMM (Belgium). Aβ40 and Aβ38 standards were purchased from rPeptide. Aβ42 calibrators' accuracy was established using CSF-based Aβ42 Certified Reference Materials (CRM). Results: CRM-adjusted Aβ42 calibrator concentrations were calculated using the regression equation Y (CRM-adjusted) = 0.89X (calibrators) + 32.6. Control samples and CSF pools yielded imprecision ranging from 6.5 to 10.2% (Aβ42) and 2.2 to 7.0% (Aβ40). None of the CSF pools showed statistically significant differences in Aβ42 concentrations across 2 different calibrator lots. Comparison of Aβ42 with Aβ42/Aβ40 showed that the ratio improved concordance with concurrent [ 18 F]-florbetapir PET as a measure of fibrillar Aβ ( n  = 766) from 81 to 88%. Conclusions: Long-term performance assessment substantiates our modified LC–MS/MS reference method for 3 Aβ peptides. The improved diagnostic performance of the CSF ratio Aβ42/Aβ40 suggests that Aβ42 and Aβ40 should be measured together and supports the need for an Aβ40 CRM.